Designing the control law on reduced‐order models of large structural systems. Issue 4 (1st October 2015) - Casciati, Fabio; Casciati, Sara
Summary: The design of a control law requires two preliminary actions: to introduce a numerical model of the system to be controlled, together with its reduced‐order approximation, and to fix the number and positions of the actuators, together with those of the sensors providing the feedback. The link between measured acceleration quantities and model variables was successfully demanded to the Kalman filter in seismic applications. When moving to wind excitation, the standard approach is no longer viable, and one meets several options, which are discussed in the paper. A timber footbridge is studied to provide a numerical example. Copyright © 2015 John Wiley & Sons, Ltd.